Business Management Simulations - a detailed industry analysis as well as recommendations for the future - Michael Batko (Serious Games Society, 2016)
Being exposed to serious games showed that some simulations widely vary in quality and learning outcome. In order to get to the bottom of best practices a detailed review of business management simulation literature was conducted. Additionally, an industry analysis was performed, by interviewing 17 simulation companies, testing a range of full and demo games, and conducting secondary research. The findings from both research efforts were then collated and cross-referenced against each other in order to determine three things: firstly, the practices and features used by simulation companies that have not yet been the subject of academic research; secondly, the most effective features, elements and inclusions within simulations that best assist in the achievement of learning outcomes and enhancement the user experience; and finally, 'best practices' in teaching a business management course in a university or company with the assistance of a simulation. Identified gaps in the current research were found to include the effectiveness of avatars, transparent pricing and the benefits of competing the simulation against other teams as opposed to the computer. In relation to the second and third objectives of the research, the findings were used to compile a business plan, with detailed recommendations for companies looking to develop a new simulation, and for instructors implementing and coordinating the use of a simulation in a business management context.